Dual surface modification of PDMS-based silicone implants to suppress capsular contracture. (August 2018) - Yoo, Byoung Yong; Kim, Byung Hwi; Lee, Jae Sang; Shin, Byung Ho; Kwon, Heeyeon; Koh, Won-Gun; Heo, Chan Yeong
Graphical abstract: Abstract: In this study, we report a new physicochemical surface on poly(dimethylsiloxane) (PDMS)-based silicone implants in an effort to minimize capsular contracture. Two different surface modification strategies, namely, microtexturing as a physical cue and multilayer coating as a chemical cue, were combined to achieve synergistic effects. The deposition of uniformly sized microparticles onto uncured PDMS surfaces and the subsequent removal after curing generated microtextured surfaces with concave hemisphere micropatterns. The size of the individual micropattern was controlled by the microparticle size. Micropatterns of three different sizes (37.16, 70.22, and 97.64 μm) smaller than 100 μm were produced for potential application to smooth and round-shaped breast implants. The PDMS surface was further chemically modified by layer-by-layer (LbL) deposition of poly-l -lysine and hyaluronic acid. Short-term in vitro experiments demonstrated that all the PDMS samples were cytocompatible. However, lower expression of TGF-β and α-SMA, the major profibrotic cytokine and myofibroblast marker, respectively, was observed in only multilayer-coated PDMS samples with larger size micropatterns (70.22 and 97.64 μm), thereby confirming the synergistic effects of physical and chemical cues. An in vivo study conducted for 8 weeks after implantation in rats also indicated that PDMS samples with larger size micropatterns and multilayer coating most effectively inhibited capsular contracture based on analyses of tissue inflammation, number of macrophage, fibroblast and myofibroblast, TGF-β expression, collagen density, and capsule thickness. Statement of Significance: Although poly(dimethylsiloxane) (PDMS)-based silicone implants have been widely used for various applications including breast implants, they usually cause typical side effects called as capsular contracture. Prior studies have shown that microtexturing and surface coating could reduce capsular contracture. However, previous methods are limited in their scope for application, and it is difficult to obtain FDA approval because of the large and nonuniform size of the microtexture as well as the use of toxic chemical components. Herein, those issues could be addressed by creating a microtexture of size less than 100 m, with a narrow size distribution and using layer-by-layer deposition of a biocompatible polymer without using any toxic compounds. Furthermore, this is the first attempt to combine microtexture with multilayer coating to obtain synergetic effects in minimizing the capsular contracture.